KEJAHATAN PASAR MODAL DALAM KERANGKA GOOD CORPORATE GOVERNANCE - Titik Suharti (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
There is always crime happened in every society, including in business community in Indonesia such as in stock exchange sector one of reason why it can happen is weak Good Corporate Governance application. In order knowing how to rule out criminal in stock exchange in Indonesia in term of Good Corporate Governance framework, the writer uses normative juridical approach so that it is known that stock exchange crime has been ruled out in Stock Exchange Law though not all of the principles included in it.